A High‐Yielding Synthesis of EIDD‐2801 from Uridine. Issue 43 (12th November 2020) - Steiner, Alexander; Znidar, Desiree; Ötvös, Sándor B.; Snead, David R.; Dallinger, Doris; Kappe, C. Oliver
Abstract : A simple reordering of the reaction sequence allowed the improved synthesis of EIDD‐2801, an antiviral drug with promising activity against the SARS‐CoV‐2 virus, starting from uridine. Compared to the original route, the yield was enhanced from 17 % to 61 %, and fewer isolation/purification steps were needed. In addition, a continuous flow procedure for the final acetonide deprotection was developed, which proved to be favorable toward selectivity and reproducibility. Abstract : An improved protocol was developed for the synthesis of EIDD‐2801, which is currently in Phase II clinical trials for the treatment of COVID‐19. The process employs uridine as starting material and proceeds through triazolation, one‐pot acetonide protection/esterification and telescoped hydroxyamination/continuous flow acetonide deprotection.